Defluffing machine for dinanath grass seeds (Pennisetum pedicellatum) - SINGH, SANJAY KUMAR; PATHAK, P K; GURJAR, BHOLURAM; KAUTKAR, SHESHRAO (The Indian Journal of Agricultural Sciences, 2025)
Traditionally, defluffing (separation of nucleus seeds from fluffy seed) of dinanath grass seeds (Pennisetum pedicellatum) is cumbersome and time consuming. Hence, a defluffing machine consisting of feeding chute, feed rollers, serrated cylinder assembly, grading unit and power transmission unit was developed considering the physical properties of the dinanath seed and evaluated its performance at ICAR-Indian Grassland and Fodder Research Institute, Jhansi (2019). The mean values of seed dimensions (length × width × thickness) for fluffy seed and nucleus seed were computed as 6.20×2.77×1.83 mm3 and 2.44×0.82×0.58 mm3 respectively. The average bulk densities of fluffy and nucleus seeds were 7.65 kg/m3 and 613.63 kg/m3 respectively. The optimum machine performance like defluffing capacity (4.9 kg/h), defluffing efficiency (92.1%) and nucleus seed recovery (22.82%) were found at 7 % moisture content and 545 rpm of serrated cylinder speed about 76 % processing cost saving using the machine could be done as compared to traditional manual defluffing. Drastic reduction (99.7%) in volume of fluffy seed was achieved after defluffing.